2018
DOI: 10.1186/s40639-018-0045-7
|View full text |Cite
|
Sign up to set email alerts
|

Compassionate care provision: an immense need during the refugee crisis: lessons learned from a European capacity-building project

Abstract: Background: The refugee crisis has resulted in massive waves of migration towards Europe. Besides sufficient and appropriate healthcare services, these vulnerable populations need kindness, respect, acceptance, empathy, and attention to basic needs. Healthcare professionals ought to have a respectful and compassionate approach to safeguard the dignity and interests of the people they care for. Aim: The overall aim of the European Refugees-Human Movement and Advisory Network (EUR-HUMAN) project was to provide g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 26 publications
(34 reference statements)
2
22
0
Order By: Relevance
“…Poor staff attitudes, as a consequence of an overburdened health system, were identified as a barrier in our data; this has support in other literature. A Europe‐wide report found that migrant women frequently felt their health care professionals were unfriendly and disrespectful 31 . They note that the language barriers, also identified in our research, exacerbated the breakdown in patient and health care professional relationship.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Poor staff attitudes, as a consequence of an overburdened health system, were identified as a barrier in our data; this has support in other literature. A Europe‐wide report found that migrant women frequently felt their health care professionals were unfriendly and disrespectful 31 . They note that the language barriers, also identified in our research, exacerbated the breakdown in patient and health care professional relationship.…”
Section: Discussionsupporting
confidence: 49%
“…They were an important meeting point, enabling women to build trust with health care workers. It is recommended that refugee women are provided information about human rights, gender equality, public health issues, and services available for refugees 31 . Health care providers in our study discussed intentions to bring in wider education to their safe spaces.…”
Section: Discussionmentioning
confidence: 93%
“…A study by Stammel et al [37] emphasizes that the received multidisciplinary treatment in a clinic had a positive effect on trauma-related symptoms as well as on the quality of life of traumatized refugees where medical doctors, psychotherapists and social workers were included in the treatment process. A study by Mechili et al [38] also emphasizes a trained multidisciplinary team in order to provide culturally adapted health assessment and compassionate health care services for migrants. For better treatment migrants must be informed about the provision of healthcare services across European countries and should stay in one host country longer.…”
Section: Discussionmentioning
confidence: 99%
“…This model has been feasibility tested and will be reported in further articles currently under development. Other known integrated healthcare models include Community Orientated Primary Care [118,119], as well as the integrated approach developed within the European Refugees-Human Movement and Advisory Network (EUR-Human) project [120].…”
Section: Highmentioning
confidence: 99%